National Information Centre for Food Science & Technology Computer Centre : Its Development, Present Activities and Future Plans - Mahakuteshwar, H. Y.; Sangameswaran, S. V. (Journal of Information and Knowledge, 1987)
Development of institutional infrastructure for computer-based information system for information processing and service for food science and technology is discussed. The hardware, configuration and the software developments have been presented in detail.